2015
DOI: 10.15740/has/tajh/10.2/278-281
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cultivars of strawberry, a temperate fruit for its adaptability as well as productivity in sub-tropical agro-climatic condition of Supaul district in Bihar

Abstract: The findings of a field trial conducted in 2012-13 and 2013-14 to assess different cultivars of strawberry in Supaul district of Bihar revealed that short day cultivars were more tolerant to insect pests than day neutral cultivars, particularly in later stage of fruit development leading to record higher yield. It was also revealed that a suitable micro-climate was required for optimum plant growth, higher crop yield and the best quality fruits. Festival was found to be the best performing variety in respect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
3
5
0
Order By: Relevance
“…The results of the present study were partially accordant with the previous reports made by Hancock et al (2001), Bussell et al (2005), Sonsteby and Heide (2008), Autuneset al (2010), Rahman et al (2013), Kim et al (2013), Rahman (2014), Ahsan et al (2014), Das et al (2015) and Belakud et al (2015).…”
Section: 3-average Fruit Weight (G)supporting
confidence: 93%
See 2 more Smart Citations
“…The results of the present study were partially accordant with the previous reports made by Hancock et al (2001), Bussell et al (2005), Sonsteby and Heide (2008), Autuneset al (2010), Rahman et al (2013), Kim et al (2013), Rahman (2014), Ahsan et al (2014), Das et al (2015) and Belakud et al (2015).…”
Section: 3-average Fruit Weight (G)supporting
confidence: 93%
“…The later values are lower than that of the present study which it found that Festival cultivar recorded 4.1 and 3.2 (cm) for fruit length and diameter, respectively (2 season's average). Das et al (2015) also found that fruit length was 3.28 and 4.19 for Sweet Charlie and Festival cultivars while fruit diameter recorded 2.27 and 3.09 (cm) for both cultivars, respectively. The later came on line with the results of present study.…”
Section: 3-fruit Length/diameter Ratio (L/d Ratio)mentioning
confidence: 65%
See 1 more Smart Citation
“…Least leaf area was recorded in cultivar Pajaro (82.37 cm 2 ) followed by Belrubi (87.38 cm²). Variation in leaf area and number of leaves per plant may be attributed to genetic make up of these varieties as has also been reported by Kumar et al, (2016), Kumar andKumar (2011) andRam et al, (2008).…”
Section: Resultssupporting
confidence: 60%
“…Plant height and spread provide an idea of the vigour of the plant and also provide information on surface available for fruit production (Kumar et al, 2016 andRani andAhmad, 2012). Variation differences in plant height and spread among strawberry varieties have also been reported by Das et al, (2015), Kumar andKumar (2011), Dolgun (2006), Rao andLal (2010), Singh et al, (2008) and Das et al, (2007).…”
Section: Resultsmentioning
confidence: 55%